Approaches to Improve the Quantitation of Oxytocin in Human Serum by Mass Spectrometry - Hering, Anke; Jieu, Beverly; Jones, Alun; Muttenthaler, Markus (Frontiers in Chemistry, 2022)
The neuropeptide oxytocin (OT) regulates several peripheral and central functions and is a molecule of interest in psychiatric diseases such as autism spectrum disorder, schizophrenia, anxiety and depression. The study of OT in human serum samples is however hampered by inconsistent sample preparation and analysis as well as low endogenous levels in blood (1–10 pM). This results in varying reports on OT’s blood level concentration and interpretations of OT’s role in different (patho)physiological states. Quantitative mass spectrometry (MS) is a highly promising technology to address this problem but still requires large sample volumes to achieve adequate sensitivity and reliability for the quantitation of low concentration compounds. We therefore systematically evaluated sample preparation methods for MS to achieve a reliable sample preparation protocol with good peptide recovery, minimal matrix effects and good overall method efficiency in line with FDA guidelines for bioanalytic method development and validation. Additionally, we investigated a strategy to improve the ionization efficiency of OT by adding charged and/or hydrophobic moieties to OT to improve the lower limit of quantitation. Optimized sample preparation in combination with OT modification with a quaternary pyridinium ion improved the sensitivity of OT by ~40-fold on a tandem triple quadrupole mass spectrometer (API4000 QTRAP), resulting in a lower limit of quantitation of 5 pM in water (linear range 5 pM – 1 mM) and 2 nM in human serum (linear range 2 nM – 1 mM) compared to 200 pM in water and 86 nM in serum with unmodified OT. This approach and protocol provide a solid foundation towards method development for OT quantitation using mass spectrometry, which should be of high value for fundamental research as well as clinical monitoring of OT concentration upon drug treatments.